Photo-accumulative composition

JP7639398B2Active Publication Date: 2025-03-05NOF CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021029139
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-25
Publication Date
2025-03-05
Estimated Expiration
2041-02-25

AI Technical Summary

Benefits of technology

【0010】 本発明の光重合性組成物(以下「本発明の組成物」と記載することがある)は、光重合によって、柔らかく且つ耐せん断性に優れた造形物(重合体)を形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639398000004
    Figure 0007639398000004
  • Figure 0007639398000001
    Figure 0007639398000001
  • Figure 0007639398000002
    Figure 0007639398000002
Patent Text Reader

Abstract

To provide a photopolymerizable composition capable of obtaining a shaped article (polymer) which is soft and excellent in shearing resistance.SOLUTION: There is provided a photopolymerizable composition which comprises: a polyalkylene glycol mono(meth)acrylate (a component (A)) represented by a formula (1): CH2=CR-COO-(AO)n-H in which a ratio wb / wf between wb and wf calculated from a chromatogram determined by gel permeation chromatography satisfies a relation of the expression (2): .25≤wb / wf≤0.90; and a monomer (a component (B)) polymerizable with the component (A) having a glass transition temperature of a homopolymer of 50°C or more in a mass ratio of the component (A) / the component (B) of 30 / 70 to 90 / 10 (the definitions of signals in the formulas (1) and (2) are as described in the specification).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photopolymerizable composition. [Background technology]

[0002] For example, photopolymerizable compositions containing compounds having ethylenically unsaturated double bonds can be solidified or cured in a short time by photopolymerization using a photopolymerization initiator, and are therefore used in a wide range of fields, such as paints, coating materials, pressure sensitive adhesives, adhesives, inkjet inks, sealing materials, sealants, dental hygiene materials, and optical materials. In particular, in recent years, as a technique for obtaining a three-dimensional object, a three-dimensional design system (CAD) is used to calculate the shape of a thin cross section on a computer, and based on the calculation results, a liquid photopolymerizable composition is irradiated with laser light or ultraviolet light to polymerize it, thereby producing a modeled object, which is called an optical three-dimensional modeling method. This optical three-dimensional modeling method can produce shapes that could not be realized by conventional methods, and has come to be widely used in the manufacture of product prototypes, architectural and construction models, medical models, and the like. It is also expected to lead to reduced development time and costs, and improved design quality.

[0003] Photopolymerizable compositions are required to have high photopolymerization sensitivity, to enable the production of three-dimensional objects in a short modeling time, and low viscosity, to provide excellent handling during modeling. In addition, three-dimensional objects obtained by photopolymerization are required to be more complex and of higher quality, and are required to have high transparency, excellent color tone without yellowing, and excellent dimensional stability with little absorption of moisture or humidity. Furthermore, a wide range of physical properties are required, from hard to soft, depending on the application.

[0004] In recent years, there has been a demand for producing soft objects using an optical three-dimensional modeling method using an inkjet system, and various compositions have been proposed. For example, Patent Document 1 discloses a color ink composition containing a colorant, an acrylate monomer AC having a homopolymer glass transition temperature of 25° C. or more and 120° C. or less, and an acrylate monomer BC having a homopolymer glass transition temperature of -60° C. or more and less than 25° C., in which the content of the acrylate monomer AC is 5% by weight or more and less than 50% by weight, and the content of the acrylate monomer BC is 20% by weight or more and less than 80% by weight, based on the total mass of the color ink composition, to produce a soft three-dimensional object. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2016 / 199611 Summary of the Invention [Problem to be solved by the invention]

[0006] For example, when manufacturing a soft object by discharging a composition while moving a modeling stage that supports the object during production, the object may be significantly deformed when an external force is applied to the object during production, and the deformed shape may not return to its original shape even after the external force is removed.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a photopolymerizable composition that can give a shaped object (polymer) that is soft and has excellent shear resistance. Here, "shear resistance" refers to the property of an object that, when its shape is changed by applying an external force, returns to its original shape when the external force is removed. [Means for solving the problem]

[0008] As a result of intensive research in light of the above-mentioned matters, the inventors have found that a shaped object (polymer) which is soft and has excellent shear resistance can be obtained from a composition containing a polyalkylene glycol mono(meth)acrylate whose elution peak in a chromatogram measured by gel permeation chromatography is asymmetric and whose molecular weight distribution is biased toward the high molecular weight side, component (A) and a polymerizable monomer, the polyalkylene glycol mono(meth)acrylate having a glass transition temperature of 50°C or higher.

[0009] The present invention based on the above findings is as follows. [1] A photopolymerizable composition containing the following components (A) and (B) in a mass ratio of component (A) / component (B)=30 / 70 to 90 / 10: (Component (A)) Formula (1): CH 2 =CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. and is calculated from a chromatogram obtained by gel permeation chromatography measurement. b And w f The ratio of b / w f But equation (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the chromatogram peak is t h and 1 / 10 of the maximum peak height (h 1 / 10 ) two retention times at t f and t b (However, t f <t b ), then w f is h andf Difference from (t h -t f ), and w b is b and h Difference from (t b -t h ) A polyalkylene glycol mono(meth)acrylate satisfying the relationship: (Component (B)) A monomer polymerizable with component (A), the homopolymer having a glass transition temperature of 50°C or higher. Effect of the Invention

[0010] The photopolymerizable composition of the present invention (hereinafter sometimes referred to as "the composition of the present invention") can form a shaped object (polymer) that is soft and has excellent shear resistance by photopolymerization. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a model of a chromatogram obtained by gel permeation chromatography measurement of a polyalkylene glycol mono(meth)acrylate, for explaining wf and wb. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In this specification, a numerical range defined using the symbol "~" includes both ends (upper and lower limits) of the symbol "~". For example, "2-4" means 2 or more and 4 or less. In this specification, "(meth)acrylate" means acrylate or methacrylate. Here, only one type of (meth)acrylate may be used, or two or more types may be used in combination. The term "(meth)acryloyl group" and the like also have the same meaning as "(meth)acrylate".

[0013] <Component (A)> Component (A) of the present invention is a compound represented by formula (1): CH 2=CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. Component (A) may be used alone or in combination of two or more kinds.

[0014] AO is at least one type of oxyalkylene group having 2 to 4 carbon atoms. That is, AO is at least one type selected from the group consisting of an oxyethylene group, an oxypropylene group, and an oxybutylene group. AO is preferably an oxypropylene group. n is the average number of moles of oxyalkylene groups added. Therefore, n may be a decimal number. n is preferably 5 to 60, more preferably 5 to 50, even more preferably 5 to 40, and particularly preferably 15 to 40.

[0015] The component (A) of the present invention is a refractive index calculated from a chromatogram (vertical axis: refractive index intensity, horizontal axis: retention time) obtained by gel permeation chromatography (GPC) measurement using a differential refractometer. b And w f The ratio of b / w f But equation (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the chromatogram peak is t h and 1 / 10 of the maximum peak height (h 1 / 10 ) two retention times at t f and t b (However, t f <t b ), then w f is h and f Difference from (t h-t f ), and w b is b and h Difference from (t b -t h ) is shown. ) is characterized by satisfying the relationship (see FIG. 1).

[0016] w b / w f When w is smaller than 0.25, the molecular weight distribution of component (A) is largely biased toward the high molecular weight side, so that the viscosity of the composition becomes high and the handling properties become poor. b / w f is preferably 0.30 or more, and more preferably 0.35 or more.

[0017] On the other hand, w b / w f If w is greater than 0.90, gelation is likely to occur during photopolymerization of the composition of the present invention. b / w f When w is greater than 0.90, the shear resistance of the shaped object (polymer) obtained by photopolymerizing the composition of the present invention becomes insufficient. b / w f is preferably 0.80 or less, and more preferably 0.60 or less.

[0018] In the present invention, w b / w f The chromatogram (vertical axis: refractive index intensity, horizontal axis: retention time) for calculating the above was obtained using an EcoSEC GPC calculation program, with a gel permeation chromatography (GPC) system equipped with an HLC-8320GPC (registered trademark), a guard column equipped with a SHODEX KF-G, and three SHODEX KF804L columns in series, a column temperature of 40° C., tetrahydrofuran as a developing solvent flowing at a flow rate of 1 mL / min, and 0.1 mL of a 0.1 wt % tetrahydrofuran solution of polyalkylene glycol mono(meth)acrylate injected.

[0019] The mass ratio of component (A) / component (B) in the composition of the present invention is 30 / 70 to 90 / 10. The mass ratio must be 30 / 70 or more to obtain a shaped product (polymer) with excellent shear resistance, and must be 90 / 10 or less to prevent the obtained shaped product from becoming excessively soft. The mass ratio is preferably 40 / 60 to 80 / 20, more preferably 50 / 50 to 80 / 20.

[0020] Component (A) can be produced by adding at least one selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide (preferably propylene oxide) to a starting material (e.g., 2-hydroxypropyl (meth)acrylate) in the presence of a composite metal cyanide complex catalyst (hereinafter sometimes abbreviated as "DMC catalyst"). Specifically, the starting material and the DMC catalyst are added to a reaction vessel, and at least one selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide (hereinafter collectively referred to as "alkylene oxide having 2 to 4 carbon atoms") is added continuously or intermittently under stirring in an inert gas atmosphere to perform addition polymerization. The alkylene oxide having 2 to 4 carbon atoms may be added under pressure or atmospheric pressure.

[0021] Average feed rate of alkylene oxide with carbon numbers of 2 to 4 teeth The amount of alkylene oxide having 2 to 4 carbon atoms is changed. do. The rate at which 5% by weight or more and 20% by weight or less of the total amount of alkylene oxide having 2 to 4 carbon atoms is fed (amount fed per unit time) is V 1 The rate during the supply of 20% by weight or more and 50% by weight or less of the total supply amount of alkylene oxide having 2 to 4 carbon atoms is V 2 The rate during the supply of 50% by weight or more and 100% by weight or less of the total supply amount of alkylene oxide having 2 to 4 carbon atoms is V 3 In one embodiment for producing component (A), V 1 / V 2 =1.1~2.0, V 2 / V 3= 1.1 to 1.5. do. In another embodiment for producing component (A), V 1 / V 2 =0.4~0.9, V 2 / V 3 = 0.5 to 0.95. do.

[0022] The reaction temperature for adding an alkylene oxide having 2 to 4 carbon atoms to the starting material is preferably 50° C. to 120° C., and more preferably 70° C. to 90° C. If the reaction temperature is lower than 50° C., the reaction rate is very slow, and if it is higher than 120° C., problems such as polymerization of the polymerizable groups in the starting material and coloring occur.

[0023] There are no particular limitations on the trace amounts of water contained in the starting materials and the alkylene oxide having 2 to 4 carbon atoms, but it is desirable that the amount of water contained in the starting materials is 0.5% by weight or less, and the amount of water contained in the alkylene oxide having 2 to 4 carbon atoms is 0.01% by weight or less.

[0024] The amount of the DMC catalyst used is not particularly limited, but is preferably 0.0001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the alkylene oxide derivative (i.e., component (A)) produced. The DMC catalyst may be added to the reaction system all at once at the beginning, or may be added in successive portions. After the polymerization reaction is completed, the DMC catalyst is removed. The catalyst can be removed by a known method such as filtration, centrifugation, or treatment with a synthetic adsorbent. In producing the component (A), a known DMC catalyst can be used.

[0025] The DMC catalyst is, for example, a compound represented by the formula (3): M a [M' x (CN) y ] b (H 2 O) c (L) d(3) (In formula (3), M and M' represent metal atoms, L represents an organic ligand, and a, b, c, d, x, and y represent positive integers.)

[0026] Examples of the metal atom (metal cation) M include Zn(II), Fe(II), Fe(III), Co(II), Ni(II), Al(III), Sr(II), Mn(II), Cr(III), Cu(II), Sn(II), Pb(II), Mo(IV), Mo(VI), W(IV), W(VI), etc. Of these, Zn(II) is preferably used.

[0027] Examples of the metal atom (metal cation) M' include Fe(II), Fe(III), Co(II), Co(III), Cr(II), Cr(III), Mn(II), Mn(III), Ni(II), V(IV), V(V), etc. Among these, Fe(II), Fe(III), Co(II), and Co(III) are preferably used.

[0028] As the organic ligand L, for example, alcohol, ether, ketone, ester, etc. can be used, and alcohol is more preferable. Preferred organic ligands are water-soluble, and specific examples include tert-butyl alcohol, n-butyl alcohol, iso-butyl alcohol, N,N-dimethylacetamide, ethylene glycol dimethyl ether (glyme), diethylene glycol dimethyl ether (diglyme), etc. A particularly preferred DMC catalyst is Zn(II) coordinated with tert-butyl alcohol. 3 [Co(III)(CN) 6 ] 2 (H 2 O) 4 (tert-Butyl alcohol) 2 It is.

[0029] In the reaction of adding an alkylene oxide having 2 to 4 carbon atoms to the starting material, other additives may be used. For example, hydroquinone (HQ), hydroquinone monomethyl ether (MQ), 2,6-di-tert-butylhydroxytoluene (BHT), di-tert-butylhydroxyanisole (BHA), α-tocopherol, β-tocopherol, γ-tocopherol, or the like may be added to the reaction system as a polymerization inhibitor. The polymerization inhibitor is preferably MQ and / or BHT, more preferably BHT. The amount of the polymerization inhibitor added is preferably 0.001 to 0.3 parts by weight per 100 parts by weight of the total of the starting material (e.g., 2-hydroxypropyl (meth)acrylate) and the alkylene oxide having 2 to 4 carbon atoms. If the amount added is less than 0.001 part by weight, the function of the polymerization inhibitor becomes insufficient, and gelation may occur during the addition of the alkylene oxide having 2 to 4 carbon atoms. On the other hand, if the amount added is more than 0.3 parts by weight, the purity of the obtained polyalkylene glycol mono(meth)acrylate may decrease.

[0030] <Ingredient (B)> Component (B) of the present invention is a monomer (excluding polyalkylene glycol mono(meth)acrylate) polymerizable with component (A) and having a homopolymer glass transition temperature of 50° C. or higher. Component (B) may be used alone or in combination of two or more. Hereinafter, the "homopolymer glass transition temperature" of component (B) may be abbreviated as "Tg".

[0031] Component (B) is preferably a compound having a (meth)acryloyl group and a Tg of 50° C. or higher, more preferably a compound having one (meth)acryloyl group in one molecule and a Tg of 50° C. or higher. Specific examples of component (B) include 4-acryloylmorpholine (Tg: 145° C.), isobornyl acrylate (Tg: 97° C.), N,N-dimethylacrylamide (Tg: 119° C.), 2-acryloyloxyethyl phthalate (Tg: 130° C.), 2-acryloyloxypropyl phthalate (Tg: 158° C.), dicyclopentanyl acrylate (Tg: 120° C.), dicyclopentanyl methacrylate (Tg: 175° C.), Examples of the acrylates include dicyclopentenyl acrylate (Tg: 120°C), isobornyl methacrylate (Tg: 180°C), adamantyl acrylate (Tg: 153°C), adamantyl methacrylate (Tg: 250°C), tert-butyl methacrylate (Tg: 107°C), cyclohexyl methacrylate (Tg: 66°C), 2-hydroxyethyl methacrylate (Tg: 55°C), and methyl methacrylate (Tg: 105°C). More preferably, component (B) is 4-acryloylmorpholine (Tg: 145°C) and / or isobornyl acrylate (Tg: 97°C). The Tg can be calculated by synthesizing a homopolymer of component (B) and subjecting the resulting homopolymer to differential scanning calorimetry (DSC). For DSC, for example, a differential scanning calorimeter manufactured by TA Instruments can be used.

[0032] The glass transition temperature of the homopolymer of component (B) must be 50° C. or higher. By using such a component (B), it is possible to prevent the shaped object obtained from the composition of the present invention from becoming excessively soft. The glass transition temperature of the homopolymer of component (B) is preferably 60° C. or higher, more preferably 80° C. or higher, and preferably 180° C. or lower, more preferably 150° C. or lower. When two or more kinds of components (B) are used, the glass transition temperature of each homopolymer of component (B) must be 50° C. or higher, preferably 60° C. or higher, more preferably 80° C. or higher, and preferably 180° C. or lower, more preferably 150° C. or lower.

[0033] <Photopolymerization initiator> The composition of the present invention preferably contains a photopolymerization initiator. The photopolymerization initiator may be used alone or in combination of two or more. The photopolymerization initiator may be a known one. Examples of the photopolymerization initiator include a radical polymerization initiator that generates radicals by the action of light (hereinafter, may be referred to as a "photoradical polymerization initiator"), and an initiator that generates an acid or a cation by the action of light (i.e., an acid generator or a cation generator). The photopolymerization initiator is preferably a photoradical polymerization initiator.

[0034] The photopolymerization of the composition of the present invention can be carried out in the wavelength range and irradiation time of light that is usually used. The amount of the photopolymerization initiator used is preferably 0.0001 mol or more and 0.1 mol or less per mol of the polymerizable functional group (meth(acryloyl) group) contained in the composition of the present invention.

[0035] <Other ingredients> The composition of the present invention may contain other components different from the above-mentioned component (A), component (B) and photopolymerization initiator, within the range that does not impair the effects of the present invention. The other components may be used alone or in combination of two or more.

[0036] The composition of the present invention may contain other polymerizable components different from the component (A) and the component (B). Examples of the other polymerizable components include vinyl acetate. The other polymerizable components may be used alone or in combination of two or more. When the other polymerizable components are used, the amount thereof is preferably 1 to 40 parts by weight, more preferably 5 to 30 parts by weight, based on 100 parts by weight of the total of the components (A) and (B).

[0037] The composition of the present invention may contain other additives different from component (A), component (B) and other polymerizable components, within the range that does not impair the effects of the present invention. The other additives may be used alone or in combination of two or more. Examples of the other additives include thermal polymerization inhibitors, antiaging agents, antioxidants, ultraviolet sensitizers, preservatives, flame retardants (e.g., phosphate ester flame retardants), surfactants, wetting and dispersing agents, antistatic agents, colorants, plasticizers, surface lubricants, leveling agents, softeners, pigments, organic fillers, and inorganic fillers. When other additives are used, the amount thereof is preferably 1 to 10 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the total of component (A) and component (B). EXAMPLES

[0038] The present invention will be described in detail below with reference to examples.

[0039] Synthesis of double metal cyanide complex (DMC) catalysts In a 2.0 mL aqueous solution containing 2.1 g zinc chloride, potassium hexacyanocobaltate K 3 Co(CN) 6 15 mL of an aqueous solution containing 0.84 g of tert-butyl alcohol was added dropwise over 15 minutes while stirring at 40°C. After completion of the addition, 16 mL of water and 16 g of tert-butyl alcohol were added, the mixture was heated to 70°C, and stirred for 1 hour. After cooling to room temperature, a filtration operation (first time) was performed to obtain a solid. 14 mL of water and 8.0 g of tert-butyl alcohol were added to this solid, the mixture was stirred for 30 minutes, and a filtration operation (second time) was performed to obtain a solid. 18.6 g of tert-butyl alcohol and 1.2 g of methanol were added to the obtained solid, the mixture was stirred for 30 minutes, and a filtration operation (third time) was performed. The obtained solid was dried at 40°C under reduced pressure for 3 hours to obtain the DMC catalyst (Zn(II) 3 [Co(III)(CN) 6 ] 2 (H 2 O) 4 (tert-Butyl alcohol) 2 ) 0.7 g was obtained.

[0040] Synthesis of component (A1) 651 g of 2-hydroxypropyl acrylate (water content 0.02 wt%), 1.0 g of DMC catalyst obtained in the same manner as in Synthesis Example 1, and 1.2 g of 2,6-di-tert-butylhydroxytoluene (BHT) were charged into a stainless steel 5-liter (capacity 4,890 mL) pressure-resistant reactor equipped with a thermometer, a pressure gauge, a safety valve, a nitrogen gas inlet tube, a stirrer, a vacuum exhaust tube, a cooling coil, and a steam jacket. After nitrogen replacement, the temperature was raised to 80°C, and 581 g of propylene oxide (methyl oxirane, water content 0.005 wt%) was added dropwise from the nitrogen gas inlet tube while stirring under conditions of 0.3 MPa or less. The pressure and temperature in the reactor were observed over time, and the pressure in the reactor was suddenly reduced 5 hours after the end of the dropwise addition of 581 g of propylene oxide. Thereafter, while maintaining the temperature inside the reaction vessel at 80°C, 1130 g of propylene oxide was gradually dripped through the nitrogen gas inlet tube under conditions of 0.5 MPa or less. 1 260g / hour, V 2 290g / hour, V 3 was 350 g / hour (V 1 / V 2 =0.9, V 2 / V 3 = 0.8). After completion of the dropwise addition, the mixture was reacted at 80°C for 0.5 hours, and then the reaction mixture was extracted from the reaction layer and filtered to remove solids, yielding a liquid component (A1). The obtained component (A1) was subjected to gel permeation chromatography measurement using the above-mentioned HLC-8320GPC (registered trademark).

[0041] Synthesis of component (A2) and component (A3) Components (A2) and (A3) were synthesized in the same manner as in the synthesis of component (A1), except that the number of moles of alkylene oxide added, or the type of alkylene oxide and its number of moles added, were changed as shown in Table 1. The obtained components (A2) and (A3) were measured by gel permeation chromatography in the same manner as above.

[0042] Synthesis of component (A') 500g of 2-hydroxypropyl acrylate, 14.5g of tin tetrachloride, 0.8g of hydroquinone monomethyl ether (MQ), and 0.2g of 2,6-di-tert-butylhydroxytoluene (BHT) were charged into a stainless steel 5-liter (capacity 4,890mL) pressure-resistant reactor equipped with a thermometer, pressure gauge, safety valve, nitrogen gas inlet tube, stirrer, vacuum exhaust tube, cooling coil, and steam jacket. After nitrogen replacement, the temperature was raised to 60°C, and 1025g of propylene oxide (methyloxirane) was added dropwise from the nitrogen gas inlet tube under conditions of 0.3MPa or less while stirring. After the dropwise addition, the mixture was reacted at 60°C for 0.5 hours, and after adding water and hexane, it was neutralized with an aqueous sodium hydroxide solution. After removing the aqueous layer, hexane and water were distilled off under reduced pressure, and the concentrate was filtered to remove solids, obtaining a liquid component (A'). The resulting component (A') was measured by gel permeation chromatography in the same manner as above.

[0043] The starting materials used in the synthesis of the above-mentioned components (A1) to (A'), b / w f The R, AO, and n in formula (1) of components (A1) to (A'), and the molecular weights of components (A1) to (A') are shown in Table 1 below. The molecular weights are calculated from the hydroxyl values ​​measured in accordance with JIS K-1557-1. As shown in Table 1 below, components (A1) to (A3) are the w b / w f The component (A') satisfies the requirements of the present invention. b / w f does not meet the requirements.

[0044] [Table 1]

[0045] Examples 1 to 6 and Comparative Examples 1 and 2 Any one of components (A1) to (A3) shown in Table 2 below, component (B), other components, and a photopolymerization initiator were charged into a 50 mL screw tube in the amounts (units: parts by weight) shown in Table 2, and thoroughly stirred with a stirrer to obtain the compositions of Examples 1 to 6 and Comparative Example 2. Also, component (A'), component (B) shown in Table 2 below, and a photopolymerization initiator were charged into a 50 mL screw tube in the amounts (units: parts by weight) shown in Table 2, and thoroughly stirred with a stirrer to obtain the composition of Comparative Example 1.

[0046] The component (B), other components, and photopolymerization initiators used in Examples 1 to 6 and Comparative Examples 1 and 2 are as follows. The "glass transition temperatures (Tg) of homopolymers" of component (B) and other components are also shown below. (Component (B)) IBX: Isobornyl acrylate (Tg: 97℃) ACMO: 4-acryloylmorpholine (Tg: 145°C) (Other ingredients) VA: Vinyl acetate (Tg: 30℃) (Photopolymerization initiator) HCPK: 1-hydroxycyclohexyl phenyl ketone

[0047] [Table 2]

[0048] Evaluation of the composition (Young's modulus measurement) The compositions of Examples 1 to 6 and Comparative Examples 1 and 2 were applied onto a glass plate using a bar coater, and an integrated light dose of 500 mJ / cm was applied using an 80 W / cm electrodeless UV lamp (H bulb). 2 A film (length 8 cm, width 2 cm, thickness 300 μm) was obtained by irradiating the film with light of 1000 nm. A tensile test was performed at a tensile speed of 50 mm / min (Shimadzu Corporation, AGS-J), the Young's modulus of the obtained film was calculated, and its softness was evaluated according to the following criteria. The results are shown in Table 3 below. <Softness evaluation criteria> ◎: Young's modulus of film is 50MPa or more and less than 500MPa ◯: Young's modulus of film is 500 MPa or more and less than 1500 MPa ×: Young's modulus of film is less than 50 MPa, 1500 MPa or more

[0049] (Evaluation of shear resistance) 5 g of the composition of Examples 1 to 6 or Comparative Example 1 was placed in a petri dish, and an electrodeless UV lamp (H bulb) of 80 W / cm was used to irradiate the composition with an integrated light intensity of 500 mJ / cm 2 A test piece was obtained by irradiating the specimen with light of 1000 nm. The obtained test piece was evaluated using a viscoelasticity measuring device MCR302 manufactured by Anton Paar and a measuring probe (cone plate, PP25). Specifically, the storage modulus G' of the test piece was measured when the shear strain γ of the test piece at 20°C was changed from 0.01 to 1000. Storage modulus G' when shear strain γ = 0.01 γ=0.01 , and the storage modulus G' at shear strain γ = 1000 γ=1000 From the following formula: Storage elasticity change rate C=G' γ=1000 / G' γ=0.01 The storage elasticity change rate C was calculated by the above method, and the shear resistance was evaluated using the obtained storage elasticity change rate C according to the following criteria. The storage elasticity modulus G' depends on the change due to an external force applied to the test piece, and the larger the storage elasticity change rate C, the better the shear resistance. The results are shown in Table 3 below. <Evaluation criteria for shear resistance> ◎: Storage elasticity change rate C is 0.80 or more ○: Storage elasticity change rate C is 0.50 or more and less than 0.80 ×: Storage elasticity change rate C is less than 0.50

[0050] [Table 3]

[0051] As shown in Tables 2 and 3, b / w fThe polymers obtained by photopolymerization of the compositions of Examples 1 to 6 using any one of the components (A1) to (A3) satisfying the requirements of the present invention are b / w f The polymer obtained by photopolymerization of the composition of Comparative Example 1 using component (A') not satisfying the above requirement shows superior shear resistance. In Comparative Example 2 using an excessive amount of component (B), a soft polymer was not obtained. [Industrial Applicability]

[0052] The photopolymerizable composition of the present invention is useful, for example, for forming a three-dimensional object by photopolymerization.

Claims

1. A photopolymerizable composition containing the following components (A) and (B) in a mass ratio of component (A) / component (B) of 30 / 70 to 90 / 10: (Component (A)) Formula (1): CH 2 =CR-COO-(AO) n -H (1) In formula (1), R represents a hydrogen atom or a methyl group, AO represents at least one oxyalkylene group having 2 to 4 carbon atoms, and when two or more types of AO are present, (AO) n The addition form of may be either block or random, and n represents the average number of moles of oxyalkylene groups added and is a number from 5 to 100. and is calculated from a chromatogram obtained by gel permeation chromatography measurement. b And w f The ratio of b / w f But, formula (2): 0.25≦w b / w f ≦0.90 (2) (In formula (2), the retention time at the maximum peak height (h) in the peak of the chromatogram is t h The height of the maximum peak is 1 / 10 of the maximum peak height (h 1/10 ) two retention times at t f and t b (However, t f <t b ), then w f is h and f The difference between (t h -t f ), and w b is b and h The difference between (t b -t h ) is shown. A polyalkylene glycol mono(meth)acrylate satisfying the relationship: (Component (B)) A monomer capable of polymerizing with component (A), the glass transition temperature of the homopolymer being 50° C. or higher and having a (meth)acryloyl group.

2. The photopolymerizable composition according to claim 1, wherein component (B) is 4-acryloylmorpholine and / or isobornyl acrylate.

3. A photopolymerizable composition according to claim 1 or 2, which is used to form a three-dimensional object by photopolymerization.

Citation Information

Patent Citations

  • Production of functionalized polyethers

    JP2001514280A

  • Hydroxy-functional, copolymerizable polyalkylene glycol macromonomer, method for manufacturing it and use thereof

    JP2008106272A

  • Active energy ray polymerizable resin composition for optical three-dimensional modelling, three-dimensional object, and base material for cell culture

    JP2020172075A

  • Active light-curable inkjet ink set for three-dimensional printing, three-dimensional printing method and three-dimensional printing system

    WO2016199611A1